2022
DOI: 10.1186/s40001-022-00750-8
|View full text |Cite
|
Sign up to set email alerts
|

MiR-199a/b-3p inhibits colorectal cancer cell proliferation, migration and invasion through targeting PAK4 and BCAR3

Abstract: Background Colorectal cancer (CRC) is one of the leading causes of cancer-related death worldwide. P21 activated kinase 4 (PAK4) and Breast cancer anti-estrogen resistance 3 (BCAR3) have been reported to be involved in numerous aspects in tumorous progression. In this study, we propose to screen multi-targeted microRNAs. (miRNAs), which simultaneously inhibit neoplastic evolution through suppressing the transcription of target genes. Methods MTT an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…A large number of studies have shown that miR-199a/b-3p is a tumor suppressor gene, which can inhibit the proliferation, invasion and drug resistance of tumor cells such as gastric cancer 32 , HCC 33 37 , breast cancer 38 , colorectal cancer 39 and other tumor cells by regulating PAK4/MEK/ERK, PAK4/BCAR3 and other signaling pathways 55 , 56 . Our analysis of TCGA data showed that the expression of miR-199a/b-3p in HCC tissue samples was significantly lower than that in adjacent tissues, and the results of HCC diagnostic ROC curve analysis also showed that miR-199a/b-3p had predictive value for HCC diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have shown that miR-199a/b-3p is a tumor suppressor gene, which can inhibit the proliferation, invasion and drug resistance of tumor cells such as gastric cancer 32 , HCC 33 37 , breast cancer 38 , colorectal cancer 39 and other tumor cells by regulating PAK4/MEK/ERK, PAK4/BCAR3 and other signaling pathways 55 , 56 . Our analysis of TCGA data showed that the expression of miR-199a/b-3p in HCC tissue samples was significantly lower than that in adjacent tissues, and the results of HCC diagnostic ROC curve analysis also showed that miR-199a/b-3p had predictive value for HCC diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…miR-199a/b-3p, which is a tumor suppressor gene, can inhibit the proliferation of gastric cancer 34 , HCC 35 – 38 , breast cancer 40 , colorectal cancer 41 , and prostate cancer 42 by regulating the PAK4/MEK/ERK signaling pathway. Additionally, it has been found miR-199a/b-3p can inhibit HCC growth, apoptosis, invasion and angiogenesis via multiple targets, such as PDCD4, CD44, CD151, VEGFA AEGFR1/2, HGF and MMP2 35 – 38 and can affect the chemical sensitivity of hepatoma cells to doxorubicin via mTOR and c-Met 39 . What's more interesting to us is that DJ-1 might be a promising target gene for miR-199a/b-3p and intersect with the Ras and PI3K/AKT signaling pathways through analysis of miRWalk, TargetScan, and TGCA databases.…”
Section: Introductionmentioning
confidence: 99%
“…BCAR3 played an important role in the metastasis and invasion of breast cancer cells and promoted the proliferation and migration of triple-negative breast cancer by regulating MET signaling[ 6 , 7 ]. The experiment by Hou et al [ 8 ] confirmed that BCAR3 knockout significantly inhibited cell migration and colorectal cancer cell invasion, but did not affect tumor cell proliferation. In contrast, high BCAR3 expression was strongly associated with a better prognosis in multiple myeloma[ 9 ].…”
Section: Introductionmentioning
confidence: 99%